Painless aortic dissection with bilateral carotid involvement presenting with vertigo as the chief complaint - Demiryoguran, N S (BMJ Group, 2006)
A 63 year‐old woman was admitted to the emergency department with vertigo, nausea, and vomiting. On arrival ,she was fully oriented and cooperative. She denied any pain in her chest, neck, back, or abdomen. A bruit was heard on both sides of her neck. Cranial computed tomography (CT) revealed no abnormality, while thoracic CT disclosed dissection in the ascending aorta, aortic arch, and bilateral common carotid arteries. After several hours, the patient underwent vascular surgery. She had an uneventful course and was discharged without any sequelae after 10 days. Vertigo is a rare presentation of aortic dissection with carotid involvement. Elderly patients presented with vertigo and nausea/vomiting should be evaluated for the condition and carotid dissection should be ruled out. Carotid bruit may be a clue to the diagnosis.